An Investigation of PSO Algorithm-Based Back Analysis on the Three-Dimensional Seepage Characteristics of an Earth Dam - Chen, Shoukai; Liu, Xinfei (Indian Geotechnical Journal, 2019)
In view of the problem of seepage safety and the character of dangerous reservoir earth dam, the 3D seepage of FEM back analysis was studied. Based on a reservoir project, the rationality of prototype observation data in recent years is analyzed, and the effective monitoring point and its observation data are selected for back analysis. The simulation calculation model is built, and the permeability coefficient of key materials and seepage characteristics of calculation area of earth dam are obtained after using particle swarm optimization (PSO) algorithm as the inversion algorithm and using FEM as the seepage field algorithm method of improved nodal virtual flux. The results shows that the PSO, which has high efficiency with back analyzing the permeability coefficient of materials in the dam and satisfactory accuracy, can meet the requirements of engineering, and a large seepage gradient in overflow point and boundary of earth dam, which is unfavorable for dam seepage stability, is produced when the problem of contact erosion is also existed in connection part of earth dam section and masonry dam section.